Effects of Distribution Zone Design on Flow Uniformity and Pressure Drop in PEMFC. Issue 9 (23rd September 2021) - Yu, Yuan; Zhan, Zhigang; He, Luyan; Yang, Xiaoxiang; Wan, Xiongbiao; Sui, Pang-Chieh; Pan, Mu
Abstract : A typical flow field plate of proton exchange membrane fuel cells has a distribution zone that connects the input ports and main channel region where major reactions take place. In this study, the effects of two distribution zone designs, i.e., the channel-ridge distribution zone (CRDZ) and dot matrix distribution zone (DMDZ), on the gas distribution uniformity and pressure drop are investigated numerically. For the flow fields with CRDZ, the theoretical mass flow rates and pressure distributions are found to agree with numerical results well. The flow rate distributions in the flow fields become more uniform when the turning angle increases to special angle. To design the flow fields with CRDZ, the channels can be arranged with simple geometry lines in the first step and then optimised with CFD considering the actual size to achieve a more uniform distribution and suitable pressure drop. For the flow fields with DMDZ, the uniformity of gas distribution depends on the shunt and dispersion effects of dot matrix, and the rectification and expansion effects of the distribution chamber. With an increase in porosity of DMDZ, the gas distribution gets better, and it is the most uniform when the distribution zone is an empty chamber.